Structural and optical properties of sol-gel derived nanocrystalline Fe-doped ZnO - Kumar S.; Mukherjee S.; Kr. Singh R.; Chatterjee S.; Ghosh A.K. (My University, 2025)
Effects of Fe doping on the structural, optical and magnetic properties of sol-gel derived Zn1-xFexO (0 ≤ x ≤ 0.06) nanoparticles have been investigated. The single-phased wurtzite structure has been characterized by XRD analysis. The nanocrystalline nature of the samples and their crystallinity has been confirmed by TEM measurements. Raman spectroscopy has been employed to study the crystalline quality and structural disorders. FTIR analysis confirms the wurtzite structure and formation of tetrahedral coordination of the oxygen ions surrounding the zinc ions. UV-Vis measurements show that the band gap is fast blue shifted in lower Fe-concentrations and after that slowly red shifted in higher Fe-concentrations. This may be attributed to the Burstein-Moss effect which is prevailed throughout the range of Fe-doping and sp-d exchange interaction that plays a role in higher Fe-concentration. Magnetic hysteresis measurement (M-H) shows that Zn0.96Fe0.04O exhibits ferromagnetic behavior at room temperature. © 2011 American Institute of Physics.